PROSES PEMBUATAN TEMPE TRADISIONAL - Alvina, Adini; Hamdani, Dany Hamdani; Jumiono, Aji (Universitas Djuanda, 2019)
Tempe is a food that is already familiar to the people of Indonesia. These foods are rich in nutritional value, especially protein. The production of tempeh in Indonesia is mostly still done in the traditional way. This is because the Tempe businessmen come from the Home Industry circles who still use non-standard equipment and production processes. The purpose of this study is to compare the way traditional and modern tempeh are produced. This tempe is made from soybeans, using hot water for soaking and cold water for washing, tapioca flour and tempe yeast (Rhizopus oligosporus) added to the fermantation process, wrapping (banana leaves or plastic). Washing and boiling soybeans using pan and langseng. This research shows that the government has provided a policy regarding the production of tempeh contained in SNI 3144: 2009, making it easier for national tempe producers to make tempe with national standards.Keywords: Creative Design, Food Safety, Halal Critical Points.